2009
DOI: 10.1007/s10342-009-0344-9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of forest patch size and ownership structure on tree stand characteristics in a highly deforested landscape of central Poland

Abstract: Forest structure is influenced by the origin, history and manner of forest management. All these aspects may affect the occurrence of many forest dwelling organisms. We investigated the simultaneous impact of forest patch size and ownership structure on selected forest characteristics in central Poland. We sampled stand composition, the DBH of particular tree species, basal area, species number and species diversity in all 32 forest patches found in a farmland-dominated area of 150 km 2 . Forest ownership stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 39 publications
3
16
1
Order By: Relevance
“…Landscape patterns displayed the highest correlations with landownership among the group of ENVIR factors (Table 2): private forests were closer to the external forest edge, in smaller forest patches and in more fragmented landscapes than public forests, consistently with our Author-produced version of the article published in Forest Ecology and Management, 2013, Vol 306, 281-291 Original publication available at http://www.sciencedirect.com doi : 10.1016/j.foreco.2013.06.064 initial assumption (Zmihorski et al, 2010;Riitters et al, 2012). This suggests private forest is more prone to the influence of the surrounding matrix, in relation to processes occurring at the forest edge (Harper et al, 2005).…”
Section: Differences In Landscape Patternssupporting
confidence: 64%
See 3 more Smart Citations
“…Landscape patterns displayed the highest correlations with landownership among the group of ENVIR factors (Table 2): private forests were closer to the external forest edge, in smaller forest patches and in more fragmented landscapes than public forests, consistently with our Author-produced version of the article published in Forest Ecology and Management, 2013, Vol 306, 281-291 Original publication available at http://www.sciencedirect.com doi : 10.1016/j.foreco.2013.06.064 initial assumption (Zmihorski et al, 2010;Riitters et al, 2012). This suggests private forest is more prone to the influence of the surrounding matrix, in relation to processes occurring at the forest edge (Harper et al, 2005).…”
Section: Differences In Landscape Patternssupporting
confidence: 64%
“…These soil differences corroborated that severe site conditions were less desirable for private ownership due to their lower suitability for agriculture (Wright et al, 2001). In addition, a substantial proportion of the private forested lands were likely to result from agricultural set-aside (Zmihorski et al, 2010). The European forest soil survey also revealed that forest soils in France were more acidic and superficially waterlogged than agricultural soils (Badeau et al, Author-produced version of the article published in Forest Ecology and Management, 2013, Vol 306, 281-291 Original publication available at http://www.sciencedirect.com doi : 10.1016/j.foreco.2013.06.064 1999).…”
Section: Differences In Abiotic Conditionsmentioning
confidence: 55%
See 2 more Smart Citations
“…This is somewhat surprising, since forest ownership structure in Poland markedly affects several forest characteristics ( _ Zmihorski et al 2010). This can be explained as the result of the distribution of 2 of the most suitable types of forest habitats for the Hazel Grouse.…”
Section: Population In a Fragmented Habitatmentioning
confidence: 96%